Effect of Hydroalcoholic Extract of Cydonia oblonga Miller (Quince) on Sexual Behaviour of Wistar Rats - Muhammad Aslam; Ali Akbar Sial (Hindawi Limited, 2014)
Cydonia oblonga Miller (quince) is regarded as a potent libido invigorator in Tib-e-Nabvi and Unani System of Medicine. This study was carried out to evaluate the aphrodisiac activity of the hydroalcoholic extract of the fruits of Cydonia oblonga Miller (quince) in Wistar rats. The extract was administered orally by gavage in the dose of 500 mg/kg and 800 mg/kg body weight per day as a single dose for 28 days. The observed parameters were mounting frequency, assessment of mating performance, and orientation activities towards females, towards the environment, and towards self. The results showed that after administration of the extract mounting frequency and the mating performance of the rats increased highly significantly P<0.01. The extract also influenced the behaviour of treated animals in comparison to nontreated rats in a remarkable manner, making them more attracted to females. These effects were observed in sexually active male Wistar rats.